Kegiatan Pemeriksaan Kadar Kolesterol pada Petugas dan Karyawan SMA Santo Yoseph, Cakung - Kosasih, Robert; Santoso, Alexander Halim; Jap, Ayleen Nathalie; Destra, Edwin; Gunaidi, Farell Christian (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Cholesterol is a lipid compound produced by the body and obtained from food, functioning to build cell membranes, produce certain hormones, and support metabolic processes in the body. Excessive cholesterol levels can increase the risk of cardiovascular diseases. This Community Service initiative aims to enhance the understanding and awareness of staff and employees at St. Yoseph High School, Cakung, regarding the risks of high cholesterol and preventive measures through routine screenings and health education. The program follows the Plan-Do-Check-Act (PDCA) approach, encompassing planning for education and screenings, conducting information sessions and cholesterol measurements, evaluating program effectiveness, and implementing follow-up actions for continuous improvement. Education on a healthy lifestyle, which includes a balanced diet, physical activity, and avoidance of alcohol and smoking, plays a vital role in maintaining normal cholesterol levels. Routine screenings are also essential for the early detection of high cholesterol risks. This initiative is expected to promote healthy behaviors and support improved workplace health by raising awareness about the importance of cholesterol prevention in the work environment.